2020
DOI: 10.3171/2019.4.jns182660
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality and length of hospital stay with craniotomy versus craniectomy for acute subdural hemorrhage: a multicenter, propensity score–matched analysis

Abstract: OBJECTIVEThe optimal surgical treatment for acute subdural hemorrhage (ASDH) remains controversial. The purpose of this study was to compare outcomes in patients who underwent craniotomy with those in patients who underwent decompressive craniectomy for the treatment of ASDH.METHODSUsing the Japan Trauma Data Bank, a nationwide trauma registry, the authors identified patients aged ≥ 18 years with ASDH who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The large ranges are exemplary for the existing variation, that is, primarily caused by patient case-mix and treatmentrelated factors [40]. Several factors that we found to be associated with an increased total LOS were also mentioned in literature: lower GCS, higher TBI severity and the presence of extracranial injury [13,62], ICP monitoring [46,61] and decompressive craniectomy [27,53].…”
Section: Length Of Staysupporting
confidence: 59%
“…The large ranges are exemplary for the existing variation, that is, primarily caused by patient case-mix and treatmentrelated factors [40]. Several factors that we found to be associated with an increased total LOS were also mentioned in literature: lower GCS, higher TBI severity and the presence of extracranial injury [13,62], ICP monitoring [46,61] and decompressive craniectomy [27,53].…”
Section: Length Of Staysupporting
confidence: 59%
“…After propensity score matching, our study showed no difference in mortality, (DC, 42.7% and CO, 37.5%, P = .10), which is consistent with other studies. 8,12,13…”
Section: Discussionmentioning
confidence: 99%
“…21 Numerous studies have examined the mortality related to the DC and CO procedures, and found increased overall mortality in the DC procedure; however, in certain studies, when confounders were adjusted or expected fatal cases were excluded, the difference in mortality between the 2 procedures were evaded. 8,28 Shilahashi and colleagues 13 recently published a study comparing DC and CO using the Japan Trauma Data Base. They utilized the propensity score matching methodology to balance the baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations